Colombia : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the authorities of Colombia. (IMF Staff Country Reports; Country Report ;, 2010)
This report focuses on Colombia's economic policy framework and the policy response to the global crisis. In recent years, Colombia's policies strengthened a strong macroeconomic performance, which helped in achieving higher tax revenues and restraint on current spending. Colombia was not affected too severely by the global crisis. The impact of the crisis was mitigated by the authorities through countercyclical monetary and fiscal policies. The monetary stance is expected to remain supportive unless there are signs of domestic demand pressures guided by the inflation targeting framework.